2003
DOI: 10.1097/00006676-200304000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Evaluation After Resection for Ductal Adenocarcinoma of the Pancreas: A Retrospective, Single-Institution Experience

Abstract: The prognosis after surgical resection of pancreatic carcinoma mostly depends on tumor factors. In this study, it was difficult to identify the determinants of long-term survival in patients with resectable tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 18 publications
3
52
0
1
Order By: Relevance
“…ROC curve analysis revealed that CA 19-9 level of more than 106 U/ml was linked to 2 year survival with 79.3% sensitivity and 74.5% specificity. Twelve month survival and survival to hospital discharge could not be predicted by CA 19-9 level (Tables 1, 2, 3). CA 19-9 level, both as a continuous variable and dichotomized, as at least 106 U/ml or more than 106 U/ml, was an independent predictor of overall survival, 2 year survival but it was not related to perioperative death (Table 4- 11). Survival analysis during the first 12 months showed that the higher level of CA 19-9 was linked to the higher risk of death in the whole analyzed group, but such a relationship could not be detected when the subgroup of patients who died during the perioperative period was excluded (Table 7-12).…”
Section: Serum Ca 19-9 Levelmentioning
confidence: 99%
“…ROC curve analysis revealed that CA 19-9 level of more than 106 U/ml was linked to 2 year survival with 79.3% sensitivity and 74.5% specificity. Twelve month survival and survival to hospital discharge could not be predicted by CA 19-9 level (Tables 1, 2, 3). CA 19-9 level, both as a continuous variable and dichotomized, as at least 106 U/ml or more than 106 U/ml, was an independent predictor of overall survival, 2 year survival but it was not related to perioperative death (Table 4- 11). Survival analysis during the first 12 months showed that the higher level of CA 19-9 was linked to the higher risk of death in the whole analyzed group, but such a relationship could not be detected when the subgroup of patients who died during the perioperative period was excluded (Table 7-12).…”
Section: Serum Ca 19-9 Levelmentioning
confidence: 99%
“…(13)(14)(15)(16)(17)(18)(19)(20) However, their prognostic value has been a matter of controversy because the studies were based on relatively small numbers of IDC patients. Hypoxia in pancreatic cancer has been reported to increase its malignant potential.…”
mentioning
confidence: 99%
“…However, these improvements do not necessarily correlate with long-term postoperative survival, probably due to the heterogeneity of the clinic-pathologic characteristics of pancreatic cancer [19].…”
Section: Discussionmentioning
confidence: 98%